2019
DOI: 10.3889/oamjms.2019.101
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Secretor Status of Blood Group Antigens in Patients with Head and Neck Cancer

Abstract: BACKGROUND: Head and neck cancers include malignancies of the scalp and neck skin, nasal cavity, paranasal sinuses, oral cavity, salivary glands, pharynx and larynx. The term ABO secretor refers to people who secrete blood group antigens in their body fluids such as saliva, sweat, tears, semen, and serum. Non-secretors refer to those who do not secrete their blood group antigens in their body fluids. The lack of blood type antigens in body discharge increases the susceptibility to certain types of diseases and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The included eight studies were assessed under 13 quality assessment criteria and were categorized as Good, Fair, and Poor studies in quality. Five studies were considered as with a good quality) [11] [12] [19] [20][21], while the other 3 were considered as with a fair quality [6] [22] [23]. Oral cancer studies were not only restricted to the buccal cavity, but ranged from head and neck cancers to cancers in buccal cavity, salivary glands, palate, tongue and pharynx.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The included eight studies were assessed under 13 quality assessment criteria and were categorized as Good, Fair, and Poor studies in quality. Five studies were considered as with a good quality) [11] [12] [19] [20][21], while the other 3 were considered as with a fair quality [6] [22] [23]. Oral cancer studies were not only restricted to the buccal cavity, but ranged from head and neck cancers to cancers in buccal cavity, salivary glands, palate, tongue and pharynx.…”
Section: Resultsmentioning
confidence: 99%
“…Oral cancer studies were not only restricted to the buccal cavity, but ranged from head and neck cancers to cancers in buccal cavity, salivary glands, palate, tongue and pharynx. Experimental group of the Iranian study had patients diagnosed head and neck cancer while the staff members of the same hospital were considered as the controls [20]. In the study conducted in Iraq, patients diagnosed with oral cancer including buccal cavity, tongue, salivary glands, oropharynx were compared with apparently healthy volunteers with no oral lesions were selected for the control [11].…”
Section: Resultsmentioning
confidence: 99%
“…In their study, Bakhtiari, Far, Alibakhshi, Shirkhoda and Anbari (2019) reported that of the oral carcinoma patients, 66.7% were non-secretors, whereas among the controls, 73.6% were secretors. A statistically significant difference was noted between the groups.…”
Section: Discussionmentioning
confidence: 96%